2017
DOI: 10.1177/107327481702400117
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Ductal Carcinoma in Situ of the Breast Based on ERBB2 Status

Abstract: Background: The molecular signature of ductal carcinoma in situ (DCIS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Some recent studies pointed out the negative prognostic value of Her2 in both DCIS and DCISM. [4749] Unfortunately, this data may be missing in cases of microinvasion if the focus does not provide enough material to be immunohistochemically tested. In fact, in our study, we could not find survival differences in DCIS or DCISM in respect to Her2 positivity, because it was available only in a limited number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies pointed out the negative prognostic value of Her2 in both DCIS and DCISM. [4749] Unfortunately, this data may be missing in cases of microinvasion if the focus does not provide enough material to be immunohistochemically tested. In fact, in our study, we could not find survival differences in DCIS or DCISM in respect to Her2 positivity, because it was available only in a limited number of cases.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Agosto-Arroyo et al. 62 found that the overexpression of TAOK1 in the ERBB2 subtype could be associated with the occurrence of invasive breast cancer. Thean et al.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 overexpression in human breast cancer indicates a risk of recurrence independent of whether the axillary node is positive or negative for micrometastases . Overexpression of HER2 is often observed (50%) in ductal carcinomas . A clear role for HER2 overexpression in the progression from ductal carcinoma in situ (DCIS) to invasive carcinoma has not been shown, although dimerization of epidermal growth factor receptor (EGFR) and HER2 induces motility …”
Section: Introductionmentioning
confidence: 99%